Teacher Professionalism And The Quality Of Student Graduates In Madrasa - novalia, sisca; Patimah, Siti; Amiruddin, Amiruddin (Journal of Advanced Islamic Educational Management, 2023)
Improving the quality of teachers is one of the fundamental factors in education that directly affects student learning achievement. The Law on Teachers and Lecturers explicitly defines teachers as professional educators with the main task of educating, teaching or guiding, directing, training, assessing, and evaluating students in early childhood education through formal education, primary education, and secondary education. According to Regulation of the Minister of Education and Culture Number 20 of 2016, Graduate Competency Standards (SKL) are criteria regarding the qualifications of graduates' abilities which include attitudes, knowledge, and skills. The type of research that will be used in this study is a qualitative approach because according to the researcher, it is very appropriate to explore the problem and find out the professionalism of teachers in improving the quality of education by using interviews, direct observation in the field, and documentation. The results showed that there are 10 indicators of professional teacher competence in their fields at MAN 1 Bandar Lampung. and these 10 indicators must be carried out by teachers to achieve an optimal teacher role in schools.